A Analisis Metode Klasik Sambungan Kayu Jepang , Untuk Penerapan Bangunan Di Kecamatan Parengan - Mushthofa, Mushthofa (Jurnal Civil Engineering Study, 2023)
Japan is a developed country in the Asian region with the nickname "The Land of the Rising Sun". Japan is a country with social and cultural matters, Japan is known for its attitude in maintaining its ancestral heritage. One of them is in terms of maintaining buildings in ancient times, such as temples that have maintained their authenticity from 1000 years ago. It is because of that attitude that Japanese people are very careful in protecting their heritage, because the building uses wood as the main construction material which is made by a special carpenter called Miyadaiku. Traditional Japanese wood technology is known for the details of the seams and joints. In the late 1980s, Gengo Matsui published a book on joints and fittings under the title "Wood Joints in Classical Japanese Architecture". In the Parengan area, the classic Japanese wood connection method can be applied if in the Parengan area there are carpenters who have the expertise to make wood joints like the classic Japanese wood joints. However, in the Parengan subdistrict, carpenters still do not have the skills of Japanese carpenters in terms of accuracy, neatness, and focus in making the connection method and require special training to gain better experience.